2013
DOI: 10.1002/hipo.22146
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of Homer1a in the rat hippocampus

Abstract: Homer1a (H1a) is an immediate early gene involved in multiple forms of synaptic plasticity. It exhibits a postnatal increase in the rat forebrain (Brakeman et al. (1997) Nature 386:284-288) and reduces the density and size of dendritic spines in hippocampal neurons (Sala et al. (2003) J Neurosci 23:6327-6337). We evaluated hippocampal H1a expression at different postnatal ages (P3, P5, P7, P9, P15, P19, P23, P35, and adult) using Fluorescence In Situ Hybridization (FISH) and qRT-PCR. Maximal electroconvulsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 64 publications
(85 reference statements)
0
26
0
Order By: Relevance
“…Postnatal forebrain expression of Homer1a increases from birth, peaking between 3 and 5 weeks [7]. Montes-Rodríguez et al [41] demonstrated that induction of Homer1a by neuronal activity was related to postnatal age. Maximal electroconvulsive shock treatment in rats only increased hippocampal Homer1a expression when applied in the second postnatal week (but not the first), which corresponds to the maturation of glutamatergic transmission required for synaptic plasticity.…”
Section: Homer1 Ieg Induction and Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Postnatal forebrain expression of Homer1a increases from birth, peaking between 3 and 5 weeks [7]. Montes-Rodríguez et al [41] demonstrated that induction of Homer1a by neuronal activity was related to postnatal age. Maximal electroconvulsive shock treatment in rats only increased hippocampal Homer1a expression when applied in the second postnatal week (but not the first), which corresponds to the maturation of glutamatergic transmission required for synaptic plasticity.…”
Section: Homer1 Ieg Induction and Regulationmentioning
confidence: 99%
“…Neuronal activity-induced expression of short Homer1 mRNA has been observed throughout brain structures known to be involved in learning and memory, including the cerebral cortex, hippocampal CA1, CA2, CA3, and dentate gyrus, striatum, and amygdala [6, 7, 16, 35-41]. The induction of Homer1a has been extensively investigated in vitro including neuronal depolarization with ionotropic glutamate receptor agonists, N-methyl-D-aspartate (NMDA), kainite, and potassium channel blockers [31], application of brain-derived neurotrophic factor (BDNF) [42], traumatic injury [43, 44], and evoking epileptiform activity with bicuculline and 4-aminopyridine [45].…”
Section: Homer1 Ieg Induction and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we conducted an experiment for the detection of the IEG Homer1a on a data set of serial images from a mouse brain. Homer1a and other IEGs (e.g., Arc, Narp, c-Fos) are transcribed rapidly following neuronal firing, and can therefore be used as markers of behaviorally driven ensemble activity following a specific event (Guzowski et al, 1999; Guzowski et al, 2005; Montes-Rodriguez et al, 2013). In the present study, we used environmental exploration to drive Homer1a expression.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Here, we describe an analysis platform written in a Matlab framework, which conveniently combines several open-source software platforms such that users may detect, display, and quantify input-output relationships in fluorescent images sampled across entire brains and in 3-D. The methods presented here include image capture and tissue collection procedures that have been previously published, however, these methods will be summarized briefly below (Montes-Rodriguez et al, 2013; Wilber et al, 2015). We demonstrate application of this approach to a variety of data sets including neuroanatomical and functional single cell activation studies in the rat brain, demonstrating that this software tool can be rapidly adapted for analysis of any nervous system marker or stain that has been serially-sectioned and block-face imaged.…”
Section: Introductionmentioning
confidence: 99%